(untitled) (ADMPG Journal, 2024)
This article aims to provide, through bibliographical and documentary research, information on the practice of public policies of the government of Paraná for micro and small companies - MSEs. Faced with such a pretentious challenge, some data were listed, corresponding only to the period of the Covid-19 pandemic, the moment in which an unprecedented crisis hit humanity, in the most diverse realities. It was considered, fundamentally, as a context and background for the development of the research, the applicability of the theme, centralized, in public policies. To guide the critical reflection, some questions were essential, namely: What were the public policies that aimed to strengthen MSEs in the pandemic period of covid-19 in Paraná? In what way or how are government actions contributing to stimulate the MSE segment in the current business and economic context? In this way, the discussions were carried out, hoping to contribute to a deepening of such an important subject, which still needs to be provoked and woven by students, teachers and other social actors, to the point of becoming a protagonist in the most diverse areas of knowledge, why not to say, to the point of highlighting the indisputable importance of MSEs, in the current business and economic context in the national panorama.